The reel allocation problem of a corrugated packaging company - Ferreira, Marcelo; Camargo, Victor Claudio Bento; de Araujo, Silvio Alexandre [UNESP] (FapUNIFESP (SciELO), 2020)
In this paper we address a reel allocation problem that appears in a corrugated cardboard packaging company. Given a production plan which incorporates customer orders and a set of reels in stock, the decision is how to allocate these reels to the corrugator to produce the ordered corrugated cardboard sheets, aiming to minimize the number of reels used, any partial consumption of reels, the unusable leftovers and the number of production stoppages. A mixed-integer mathematical model is proposed and computational tests were performed using instances generated based on real data. The computational results show that the proposed mathematical model is consistent with the reality of the studied company and brings interesting insights that can be used in the decision-making.
Keywords: Corrugated packaging industry; Corrugator; Mathematical modeling; Mixed-integer programming; Reel allocation problem